Certification of citrus in Italy - Savino V.; D'Onghia A.M. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
An account is given of the evolution of the Italian legislation in the field of production and marketing of propagating material of citrus. The organisation of the certification procedure for the production of nursery material is illustrated based on the Ministerial Decree of 29 October 1993. While waiting for the enforcement of the above Decree, some source plants are temporarily utilized since they are free from tristeza, psorosis complex, concave gum, cristacortis, impietratura, infectious variegation, stubborn, cachexia and exocortis diseases. In Apulia the premultiplication step has been initiated and the regional certification scheme is currently being recognized. The possibility of establishing increase blocks also during the phases of premultiplication so as to meet the demands of material during the first years of activity of the system is included.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)